PENGARUH KOMPETENSI DOSEN DAN LINGKUNGAN KERJA PADA KINERJA DOSEN DENGAN MOTIVASI SEBAGAIVARIABEL PEMEDIASI DI MASA PANDEMI - Ririsma Sihombing; M Rachman Mulyandi (Universitas Negeri Medan, 2022)
The Effect of Lecturer Competence and Work Environment on Lecturer Performance with Motivation as a Mediating Variable in the Pandemic Period. This research is motivated by the atmosphere and conditions that the world is experiencing at the moment the Covid-19 pandemic. This outbreak has had a major impact on many aspects, especially learning. The author conducted research on the effect of competence and work area on performance by using motivation as a mediating variable during the pandemic. The survey will be tried on lecturers who have taught up to 124 respondents during the pandemic. The illustration-taking method used is a targeted illustration and the information collection used is a 5-step Likert scale questionnaire distributed online in the form of Google Forms. Information was analyzed with SPSS for descriptive analysis and SMART-PLS for SEM analysis. The results of this research show that competence and work area indirectly affect performance through motivation as a mediating variable. Competence and work area have a positive impact on performance. Competence and work area have a positive influence on motivation. Motivation has a positive effect on performance.